SARS-COVID-19 antibodies in pregnant women at a level III hospital in Peru - Guevara-Ríos, Enrique (2020)
Introduction: COVID-19 disease spreads rapidly. Seroprevalence in pregnant women entering for hospitalization and clinical characteristics in this type of population in Peru is not known. Objective: To determine the prevalence and clinical-epidemiological characteristics of pregnant women with anti-SARS-CoV-2 antibodies at a level III hospital in Peru. Methods: Observational and cross-sectional study performed at the National Maternal Perinatal Institute of Peru. Pregnant women admitted for hospitalization were screened for COVID-19 infection. Results of anti-SARSCoV-2 serological tests and information on maternal and perinatal characteristics were obtained. Data analysis was performed using descriptive statistics and 95% confidence intervals. Results: In 2 419 pregnant women screened we identified a prevalence of 7.0% of anti-SARS-CoV-2 antibodies (95% IC: 6.1% to 8.1%), including IgM in 10% (95% IC: 6.1% to 15.8%), IgM / IgG in 78.8% (95% IC: 71.8% to 84.6%), IgG in 11.2% (95% IC: 7.0% to 17.1%). 89.4% of the seropositive pregnant women were asymptomatic. Most frequent complications were premature rupture of membranes (11.8%) and preeclampsia (6.5%). No association was found between clinical and epidemiologic characteristics and type of serological response to SARS-CoV-2 (p > 0.05). Conclusions: Pregnant women had prevalence of anti-SARS-CoV-2 antibodies of 7.0% on admission to the hospital; most of them were asymptomatic. There was no association between clinical-epidemiological characteristics analyzed and type of anti-SARS-CoV-2 antibody response.